2023
DOI: 10.3389/fimmu.2023.1062590
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals the potential crosstalk genes and immune relationship between IgA nephropathy and periodontitis

Abstract: BackgroundIt is well known that periodontitis has an important impact on systemic diseases. The aim of this study was to investigate potential crosstalk genes, pathways and immune cells between periodontitis and IgA nephropathy (IgAN).MethodsWe downloaded periodontitis and IgAN data from the Gene Expression Omnibus (GEO) database. Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were used to identify shared genes. Then, Gene Ontology (GO) and Kyoto Encyclopedia of Genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This may reveal that CD8 T cells and NK cells activated in the kidneys of IgAN patients may promote disease progression. Recent studies have suggested that T cells and their cytokines are involved in posttranslational modi cation of IgA1 hinge region [32,33]. Peng et al demonstrated that Th cell disorder is correlated with proteinuria in IgAN [34].…”
Section: Discussionmentioning
confidence: 99%
“…This may reveal that CD8 T cells and NK cells activated in the kidneys of IgAN patients may promote disease progression. Recent studies have suggested that T cells and their cytokines are involved in posttranslational modi cation of IgA1 hinge region [32,33]. Peng et al demonstrated that Th cell disorder is correlated with proteinuria in IgAN [34].…”
Section: Discussionmentioning
confidence: 99%
“…We used R language for bidirectional clustering analysis of the union and samples of differential genes of all treatments [54]. Clustering was performed based on the expression levels of a given gene in different samples and the expression patterns of different genes in the same sample, distance was calculated by the Euclidean method, and clustering was performed by the hierarchical clustering maximum distance method (complete linkage) [55].…”
Section: Transcriptome Analysis Of T Camphoratus Myceliamentioning
confidence: 99%
“…Periodontitis is a common chronic infectious and inflammatory disease affecting people worldwide. Its etiology mainly includes the direct damage of the periodontal tissues by bacteria and the immune disorder of the host caused by bacteria [ 1 ]. Periodontitis is distinguished by enduring inflammation of the tissues that support the teeth, destruction of the periodontal ligaments, and progressive loss of alveolar bone around the teeth [ 2 ].…”
Section: Introductionmentioning
confidence: 99%